Evaluating the use of interactive virtual reality technology with older adults living in residential aged care. Issue 3 (May 2020) - Baker, Steven; Waycott, Jenny; Robertson, Elena; Carrasco, Romina; Neves, Barbara Barbosa; Hampson, Ralph; Vetere, Frank
Highlights: Virtual reality in aged care engages residents who might otherwise self-isolate. Residents enjoyed the richer interactions and variety offered by virtual reality. Results suggest residents with dementia may react adversely to head mounted displays. Abstract: Background and objectives: As technologies gain traction within the aged care community, better understanding their impact becomes vital. This paper reports on a study that explored the deployment of virtual reality (VR) as a tool to engage older adults in Residential Aged Care Facilities (RACF). The paper has two aims: 1) to identify the benefits and challenges associated with using VR with residents in aged care settings, and 2) to gather the views of older adult residents in RACF about the potential uses of VR in aged care. Research design and methods: Five RACF residents and five RACF staff members took part in an intensive two-week evaluation of a VR system. Qualitative data was collected from multiple interviews and via researcher notes and video recordings made during the VR sessions. Results: Results highlight the usability issues that impacted on the aged care residents' ability to use interactive VR technology and the potential negative impact head mounted displays can have on those living with dementia; the role that VR can play in engaging residents who might otherwise self-isolate, and how this can extend to increased engagement with family and friends. Discussion and implications: We discuss the design challenges that will need to be met in order to ensure that interactive VR technology can be used by residents living in aged care, and the potential for VR to be used as a tool to improve the quality of life of some older residents, particularly those for whom traditional social activities do not appeal.